Peran Guru Dalam Mengembangkan Sosial Emosional Anak Di Tk Darul Muttaqin Desa Bulu Sari Kecamatan Bumi Ratu Nuban Lampung Tengah - Siti Nur Kholifah; Revina Rizqiyani (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2022)
Social-emotional development is critical in the process of child development which is formed through the developments obtained in a learning process both from the family environment, friendship environment, and school environment. In developing children's social-emotional, teachers have a very important role in developing children's social-emotional at school. This study aims to find out how the role of the teacher in developing children's social-emotional in Darul Muttaqin Kindergarten, Bumi Ratu Nuban District, Central Lampung. This type of research uses descriptive qualitative field research, which was conducted at Darul Muttaqin Kindergarten, Bumi Ratu Nuban District, Central Lampung. The data sources used are primary data sources and secondary data sources. The data collection method used is interview, observation and documentation. The data analysis techniques used are data reduction, data presentation, and data verification. To test the validity of the data using source triangulation and technical triangulation. Based on the results of the research and analysis of the data obtained, it can be concluded that in developing the social emotionality of children in Kindergarten Darul Muttaqin, Bumi Ratu Nuban District, the teacher acts as an educator, supervisor, manager, innovator, communicator and motivator in order to develop children's social emotional development so that they can develop optimally. Keywords: teacher's role, social emotional development, early childhood